التأثيرات النسيجية المرضية البواغ فطر Tilletia المسبب لمرض التفحم المغطى في الحنطة عمى الرئة والطحال والكبد والكمية لمفئران المختبرية - كاظم ايمان جواد; العاني سعود رشيد; عبد الباقي نعمت جميل (Al-Nahrain Journal of Science, 2018)
Injection of 0.1 % spore suspension of Tilletia (bunt causal agent) via intraperitonal or via oral of experimental mice caused histopathological effects in all the organs (lung, spleen, liver and kidneyof treated mice with more damage by used intraperitonal injected. The damages observed in liver injected in bloody bleeding and necrosis in the tissue beside edematous break with increase in kupffer cells and wideness in sinusoids of the liver in treated mice.